Antioxidant peptides released from gastrointestinal digestion of "Stracchino" soft cheese: Characterization, in vitro intestinal protection and bioavailability. (October 2016) - Pepe, Giacomo; Sommella, Eduardo; Ventre, Giovanni; Scala, Maria Carmina; Adesso, Simona; Ostacolo, Carmine; Marzocco, Stefania; Novellino, Ettore; Campiglia, Pietro
Highlights: Gastro intestinal digestion of Stracchino soft cheese was carried out. Peptide fractions were tested for their antioxidant potential on intestinal epithelial cells (IEC-6). UHPLC-MS/MS analyses revealed the presence of two abundant β-Casein peptides in the most active fraction. Peptides EAMAPK and AVPYPQ were further synthesized and separately tested showing activity in the range of 5–150 µg/mL. Bioavailability studies were carried out on Caco-2 monolayer cells. Abstract: Stracchino is a typical Italian soft cheese, widely consumed and appreciated for its flavour and freshness. With the aim to follow the release of health-promoting peptides, an in vitro gastro-intestinal digestion of Stracchino was carried out. The digest was fractionated by semi-preparative RPLC and tested for its antioxidant properties in H2 O2 -treated intestinal epithelial cell line (IEC-6). The most active fraction was characterized by UHPLC-MS/MS, showing the presence of two abundant β-casein hexapeptides: EAMAPK (f: 115–120) and AVPYPQ (f: 192–197), which were synthesized and tested, showing antioxidant activities in a wide concentration range (5–150 µg/mL), involving ROS reduction, SOD expression increase and Nrf2 antioxidant response activation. Hence, bioavailability studies were carried out through Caco-2 monolayers cells on the two hexapeptides, which revealed a significative concentration in the basolateral side. The results highlight the potential of Stracchino as health promoting food, and the possible employment of casein peptides in nutraceutical formulations.